Plastome evolution and organisation in the Hoya group (Apocynaceae) - Michele Rodda (Nature Portfolio, 2021)
Abstract The genus Hoya is highly diverse and many of its species are popular ornamental plants. However, the relationships between Hoya and related genera (the Hoya group) are not fully resolved. In this study, we report 20 newly sequenced plastomes of species in the Hoya group. The complete plastomes vary in length from 175,405 to 178,525 bp while the LSCs vary from 90,248 to 92,364 bp and the complete SSCs vary from 2,285 to 2,304 bp, making the SSC in the Hoya group one of the shortest known in the angiosperms. The plastome structure in the Hoya group is characterised by a massive increase in the size of the inverted repeats as compared to the outgroups. In all ingroup species, the IR/SSC boundary moved from ycf1 to ndhF while this was not observed in outgroup taxa, making it a synapomorphy for the Hoya group. We have also assembled the mitogenome of Hoya lithophytica, which, at 718,734 bp, is the longest reported in the family. The phylogenetic analysis using exons from 42 taxa in the Hoya group and three outgoups confirms that the earliest divergent genus in the Hoya group is Papuahoya, followed by Dischidia. The relationship between Dischidia and the clade which includes all Hoya and Oreosparte taxa, is not fully supported. Oreosparte is nested in Hoya making it paraphyletic unless Clemensiella is recognised as a separate genus.